Analyzing The Use of Space Prepositions in Vice Articles for EFL Learners - Irnella Nopriyanti; Lilia Indriani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
Prepositions are the words that used nouns in phrases providing information about time, place, and other relations that involving actions and things. It can be describing that prepositions have an essential role in writing. In this case, EFL students must understand the use of prepositions, which will improve their writing and reading skills. The platform that is used for this research is from the Vice website's articles. This research aimed to examine prepositions of space in the Vice website that contains many articles using descriptive qualitative methods. This analysis also determines the number of space prepositions used, the functions, and the most widely used prepositions of space in the Vice articles.